Development of a novel family of antifungal agents based on a quinone methide oxime framework - Monika Janeczko; Maciej Masłyk; Oleg M. Demchuk; Antonina Kurowska-Okoń; Mateusz Kwaśnik; Kamila Górka; Aleksandra Martyna; Béatrice Foll-Josselin; Sandrine Ruchaud; Stéphane Bach; Przemysław Woliński; Radomir Jasiński; et al. (Scientific Reports)
Abstract Given the widespread occurrence of fungal infections, the phenomenon of fungal drug resistance, and the limited number of systemic antimycotic therapies, novel chemicals should be developed to control pathogenic fungi. We propose using quinone methide oximes as a novel framework for developing a novel class of antifungal agents. Compound 2 was destroyed mature biofilms at the concentration of 0.5 µg/mL (MIC/4) and prevented hyphal growth of Candida albicans at 0.125 µg/mL (MIC/16). The chemical applied at the concentration of 16–128 µg/mL inhibited the growth of the majority of the clinical isolates of Candida used, including those exhibiting resistance towards systemic drugs. Our safety studies performed with the use of normal human cells revealed that compound 2 was not toxic at the antifungal concentrations tested. Surprisingly, compound 2 showed low inhibitory activity against a set of protein kinases in comparison with its parental compound 1.